Theories of Central European Integration in Croatian Politics and Culture (1848–1971) - Kljaić, Stipe (Great Theorists of Central European Integration, 2023)
This chapter presents authors involved in Croatian politics and culture between 1848 and 1971 who advocated for Central European integration. In discussing these figures, we examine Austro-Slavism, Croatian-Hungarian unionism, efforts to create the Danube confederation (1918–1945), and the state of Central Europe during the Cold War before the crucial events of the 1980s. After the revolutionary year of 1848 shook the traditional constitutional ties between Croatia and Hungary, Austro-Slavism appeared and offered an alternative to the old Croatian-Hungarian unionism. Austro-Slavism sought to connect the Croats with other West Slavic and South Slavic peoples on the principles of linguistic and ethnic bonds, attempting to form a new political alliance on a different basis than that with the Hungarians. Different forms of Slavism, including Croatian and Hungarian nationalism, led to conflicts between Croats and Hungarians especially in 1848, but the Croatian-Hungarian settlement of 1868 revived the Croatian-Hungarian union, which had suddenly been broken in 1848. After the breakdown of the Monarchy, Emperor Charles I advocated for the restoration of the Habsburg Monarchy. As he failed to attain the Hungarian throne in 1921, his plans remained unfulfilled. A little later, his successor, the Archduke Otto von Habsburg, revived interest in the Danube confederation as a response to Hitlerism and Stalinism and its expansionism towards Central Europe and attempted to lobby the American and British establishments in favour of a Central European confederalism. These initiatives generated interest in Croatia, which was to be integrated into the project. Among those who paid closest attention to the plans were Catholic and conservative groups in exile because the Danube Confederation was to be formed on the basis of anticommunism and anti-sovietism. Due to the contest between the Soviet Union and Yugoslavia in 1948, certain circles of Croatian emigration stopped writing about the idea of a Central European Danube confederation and began to place their expectations on the disintegration of Yugoslavia and the creation of an independent Croatian state. However, the Prague Spring of 1968 and next the Croatian Spring in communist Yugoslavia brought backinterest in Central European issues among Croatian emigrant circles. Already in the early 1970s, it was speculated that the Eastern Communist bloc would not be able to survive the blows of the Central European nations’ national movements. The political right and left in Croatia during the second half of the 20th century were fiercely divided over Central European integration. While the right advocated for an independent Croatian state, which would have been open to Central European integration, the left wanted to see Croatia as an integral part of the Yugoslav state and the Balkan region. Unfortunately, due to the limited scope of the chapter, several important issuescould not be discussed, such as the relationship between Croatian President Franjo Tuđman and the Visegrad Group in the 1990s during the time of democratic Croatia.KEYWORDS: Central European Integration, Austro-Slavism, Croatian-Hungarian Unionism, Danube Confederation, Milan Šufflay, J. Josip Strossmayer, Ivo Lendić.